2018
DOI: 10.1121/1.5032126
|View full text |Cite
|
Sign up to set email alerts
|

Song recorded near a super-group of humpback whales on a mid-latitude feeding ground off South Africa

Abstract: Humpback whales (Megaptera novaeangliae) are well known for their complex song which is culturally transmitted and produced by males. However, the function of singing behavior remains poorly understood. Song was observed from 57 min of acoustic recording in the presence of feeding humpback whales aggregated in the near-shore waters on the west coast of South Africa. The structural organization of the song components, lack of overlap between song units, and consistency in relative received level suggest the son… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Satellite tagging studies have shown that humpback whales from breeding stock A and B both migrate to the eastern part of the South Atlantic 71,72 and might therefore both contribute to the songs recorded in this study. Single song phrases detected in this study were also documented for song sequences recorded off the Western Cape of South Africa 12,32 . In order to fully understand the eventual sharing of common feeding areas among humpback whales from different breeding stocks and the cultural transmission of song among them, further comparative analyses of songs from the breeding grounds and the ASSO are necessary.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Satellite tagging studies have shown that humpback whales from breeding stock A and B both migrate to the eastern part of the South Atlantic 71,72 and might therefore both contribute to the songs recorded in this study. Single song phrases detected in this study were also documented for song sequences recorded off the Western Cape of South Africa 12,32 . In order to fully understand the eventual sharing of common feeding areas among humpback whales from different breeding stocks and the cultural transmission of song among them, further comparative analyses of songs from the breeding grounds and the ASSO are necessary.…”
Section: Discussionsupporting
confidence: 57%
“…To date, two studies have presented song recordings from Antarctic waters comprising four days from two sites 13,20 . One further study collected acoustic data near a humpback whale 'super-group' off western South Africa and describes the song that was recorded there 32 . These studies showed that the identification and structural analysis of humpback whale song from austral feeding grounds can provide valuable information on humpback whale behavioural ecology and potentially even offer insight into the breeding stock origin of humpback whale males present in the feeding areas.…”
mentioning
confidence: 99%
“…In contrast to coastal South Africa, song was not clearly detected at Vema during the recording period. This was unexpected as humpback whales are generally common in the South Atlantic Ocean (Wedekin et al, 2017), especially during their southward migration between September and November (Barendse et al 2011) when they are known to sing (Ross Marsh et al, 2020;Gridley et al, 2018;Hawkey et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The low numbers and inconsistent acoustic detections, combined with the shift in detections from the western to eastern hydrophone from 28th October to 4th November 2019, suggest that only a few vocalizing humpback whales were present, which is consistent with the low number of visual sightings. No clear humpback whale song was detected, despite extensive recording of song at this time of year off the coast of South Africa where animals are migrating south and lingering to feed in the Benguela ecosystem (Gridley et al ., 2018; Ross-Marsh et al ., 2020). All usable acoustic detections at Vema Seamount were of non-song vocalizations which typically occur during mating, socializing and feeding (Dunlop et al ., 2007; Rekdahl et al ., 2013, 2015).…”
Section: Discussionmentioning
confidence: 99%